Effects of Morton's foot on vertical jump, static and dynamic balance performances of modern dancers - Agopyan, A.; Ersoz, A.; Topsakal, N. (EDIZIONI MINERVA MEDICA, 2011)
Aim. The purpose of this study was to examine the effects of Morton's Foot on vertical jump, static and dynamic balance performances of modern dancers. Methods. The participants were 14 undergraduate modern dancers and were divided into two groups according to their foot type: Morton's Foot (ME, N.=7) and non Morton's Foot (NMF, N.=7). Static balance, dynamic balance, two vertical jump (squat jumps in parallel and in first position) performances and the second toe length in relation to the hallux were recorded, and the results of these two groups were compared. Results. The results showed that the duration of static balance in the dominant leg was longer in both groups. However, there was no bilateral difference in standing duration in single leg static balance on the left and the right leg within each group (P>0.05). The squat jump height, flight time and duration in dynamic balance were found to be higher in the NMF group compared to the ME group but these differences were not statistically significant (P>0.05). On the other hand, the NMF group dancers were able to stay longer in static balance on their left and right foot than the NMF group dancers were and these were statistically significant (P<0.05). Conclusion. It was concluded that the ME type did not have a negative effect on bilateral static balance development, dynamic balance and vertical jump performance. However, the ME could be a negative factor influencing the performance of static balance on single-leg-stance of modern dancers. These effects should be considered when researchers or clinicians are working on one foot static balance measurements.
Keywords: Foot deformities, acquired; Dancing; Postural balance; STRESS-FRACTURES; BALLET DANCERS; 2ND METATARSAL; LENGTH; STABILITY; BEHAVIOR; INJURY; BASE; TOE; General & Internal Medicine; Sport Sciences